2015
DOI: 10.1016/j.ultramic.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Sub-micron resolution selected area electron channeling patterns

Abstract: Collection of selected area channeling patterns (SACPs) on a high resolution FEG-SEM is essential to carry out quantitative electron channeling contrast imaging (ECCI) studies, as it facilitates accurate determination of the crystal plane normal with respect to the incident beam direction and thus allows control the electron channeling conditions. Unfortunately commercial SACP modes developed in the past were limited in spatial resolution and are often no longer offered. In this contribution we present a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…6 gives an example of a SEM image acquired in electrons channeling conditions (ECCI mode), on the crept sample from LG1 batch, according to the method described in Refs. [19,21,22]. On this image, small clear lines can be clearly distinguished within the grains: these lines reveal free dislocations (pointed by black arrows), as well as sub-grain boundaries (pointed by white arrows).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…6 gives an example of a SEM image acquired in electrons channeling conditions (ECCI mode), on the crept sample from LG1 batch, according to the method described in Refs. [19,21,22]. On this image, small clear lines can be clearly distinguished within the grains: these lines reveal free dislocations (pointed by black arrows), as well as sub-grain boundaries (pointed by white arrows).…”
Section: Discussionmentioning
confidence: 91%
“…To obtain a suitable surface state for EBSD and ECCI characterizations the final polishing step was performed with a 0.04 mm silica aqueous solution. Polished samples were observed by scanning electron microscopy (SEM) in backscattered electrons (BSE) mode, using a FEI Nova NanoSEM 450 microscope for standard SEM imaging and EBSD characterizations, and a ZEISS AURIGA 40 microscope for examinations in ECCI conditions [19]. The characterization of porosity in the as-manufactured reference samples was performed on surfaces of about 0.05 mm 2 by image analysis, using the Olympus AnalySIS software.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…In particular, the features revealed by this improved precision are shown to be dislocations by comparison with high resolution ECCI and it is shown that it is possible to quantify the misorientations around such features. The ECCI signal (Wilkinson & Hirsch, 1997; Crimp et al ., 2001; Trager‐Cowan et al ., 2007; Picard et al ., 2012; Mansour et al ., 2014; Zaefferer & Elhami, 2014; Guyon et al ., 2015) is produced when a sample is placed so that a crystal plane or planes are at, or close to, the Bragg angle with respect to the incident electron beam. Any deviation in crystallographic orientation or in lattice constant due to local strain will produce a variation in contrast in the resultant ECCI micrograph.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is based on an innovative procedure for collecting high angular and spatial resolution (about 500 nm) selected area channeling patterns (HR-SACPs) on the GEMINI-type electron column [26]. This technique, called Accurate ECCI (A-ECCI), was applied to unambiguously characterize screw dislocations in fine-grained IF-Steel using the gÁb = 0 invisibility criterion [17].…”
Section: Introductionmentioning
confidence: 99%